I'll Buy That! Cybersecurity in the Internet Marketplace. - Pfleeger, S.L.
Interviews with chief security officers in the Internet supply chain (those companies that provide Internet services or encourage people to use the Internet) reveal dramatically different attitudes about corporate cybersecurity. The authors' preliminary investigation suggests that a company's market discipline explains these differences.